Peningkatan Kemampuan Pemahaman Matematis Siswa Sekolah Menengah Pertama Melalui Problem Based Learning (PBL) Dan Direct Instruction (DI) - ., Maryati (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2015)
The aim of the research is to know the comparison of students Mathematic understanding between the students who have been treated by using Problem Based Learning Method and Direct Instruction Method, students attitude on learning process as well. The resea rch design was static Group Pre test - Post Test Design. The population was the IX grade students of Margahayu Yunior High School – Bandung Regency. The sample were the students of IX B and IX C. Each class consisted of 30 students. In this research, experim ental group has been treated by using Problem Based Learning Method and control group has been treated by using Direct Instruction. The test instrument used was the ability of mathematic understanding test and attitude scale. Based on the data analysis, th e result is no significant diversification of students mathematic understanding between the students who have been treated by using Problem Based Learning Method and Direct Instruction. Whereas the students attitude, there was positive attitude when they were treated by using Problem Based Learning Method